Case Report: Congenital diaphragmatic hernia associated with esophageal atresia and tracheoesophageal fistula - Zhang, Feihong; Wu, Yang; Zhang, Li; Xia, Bin (Frontiers in Surgery, 2023)
The coexistence of congenital diaphragmatic hernia and esophageal atresia with or without tracheoesophageal fistula is extremely rare; only 36 cases have been reported. We report a case of a preterm male newborn infant with left congenital diaphragmatic hernia, esophageal atresia, and tracheoesophageal fistula and review 27 related cases.